A copper(i)-catalyzed three-component reaction of triethoxysilanes, sulfur dioxide, and alkyl halides. Issue 3 (25th January 2016) - Zheng, Danqing; Mao, Runyu; Li, Zhiming; Wu, Jie
Abstract : A copper(i )-catalyzed three-component reaction of triethoxysilanes, DABCO·(SO2 )2, and alkyl halides is reported. This transformation provides a facile route to sulfones under ligand-free conditions catalyzed by copper(i ) oxide. The insertion of sulfur dioxide is efficient, and both triethoxyarylsilanes and triethoxyalkylsilanes are practicable during the coupling process. Abstract : A copper(i )-catalyzed three-component reaction of triethoxysilanes, DABCO·(SO2 )2, and alkyl halides is reported for the first time. This transformation provides a convenient and facile route to sulfones under ligand-free conditions catalyzed by copper(i ) oxide. The insertion of sulfur dioxide is efficient, and both triethoxyarylsilanes and triethoxyalkylsilanes are practicable during the coupling process. A plausible mechanism is proposed, supported by theoretical calculations.